Assessment of the Mechanical Properties of High Strength Mortar Incorporating Silica Fume and Graphene Nanoplatelets: Experimental and Mathematical Modeling - Salah H.A.; Mutalib A.A.; Algaifi H.A.; Yahya I.B.; Yusof M.A.I.; Sakib N.; Elsayed M. (MDPI, 2024)
Cement-based mortar is recognized as a popular and cost-effective material for the rehabilitation and repair of reinforced concrete structures. However, the development of high-performance cement-based mortar is in high demand in order to not only enhance compressive strength but also to prolong the mortar lifespan and minimize maintenance costs as much as possible. In the current study, high-strength mortars incorporating both silica fume and graphene nanoplatelets (GNPs) were investigated and evaluated based on compressive and flexural strength. The graphene powder was added in amounts ranging from 0.5% to 2%, by cement weight, while silica fume was added as a partial replacement for cement (10%). The optimal content of the graphene was determined using response surface methodology (RSM). In addition, field emission scanning electron microscopy (FESEM) was used to assess the proposed mortar at the micro-scale level. The outcome revealed that the graphene-based mortar imparted superior mechanical properties compared to the control mixture. The compressive and flexural strength of the mortars containing 10% silica fume and 1% graphene increased by 33% and 35%, respectively. This positive result was attributed to the refinement of the nanopores and tiny cracks by the inclusion of GNPs, which was supported by microstructure testing. The RSM model was also shown to be capable of optimizing and predicting compressive and flexural strength with less error. It is possible to conclude that graphene-based high-strength mortar will serve as a sustainable material in the near future. 2023 by the authors.